Optimizing crashworthiness design of square honeycomb structure - Li, Meng; Deng, Zong-quan; Guo, Hong-wei; Liu, Rong-qiang; Ding, Bei-chen (Journal of Central South University, 2014)
To provide theoretical basis for square honeycombs used as crashworthy structures, energy-absorption properties of metal square honeycombs and the size optimization were performed. Specific energy absorption (SEA) was defined as the energy absorbed by the honeycomb structure per unit volume. This parameter was often used for determining the crashworthiness of thin-walled structures. In order to find the most optimized metal square honeycomb structure with the maximum SEA and the lowest peak stress, the cell length and the foil thickness of the metal honeycombs were optimized, with a low peak stress and a high SEA set as the two primary objectives. The pre-processing software Patran was used to build FE models, and the explicit solver LS-DYNA was employed to perform the crashworthiness analyses. The results show that the square honeycomb exhibits good energy absorption performance in some cases. The geometry is effective using 16.8% less buffer structure volume than the hexagonal honeycombs with a peak stress limitation of 1.21 MPa.